The Important Implications of Patient Centered Care in Anesthesia: Literatur Review - Isnafianing Palupi; Elsye Maria Rosa (Nusantara Science and Technology Proceedings, 2024)
This literature review study is motivated by the problem of implementing patient centered care in anesthesia services in hospitals which is still rarely carried out. However, the application of patient centered care in anesthesia has several important implications. This literature aims to theoretically analyze the important implications of patient centered care in anesthesia. The literature review method was carried out on twelve articles obtained from two databases, namely PubMed and Science Direct. The results of the literature review are that the application of patient centered care anesthesia has several important implications. The results of the review article are: 1) Reducing stress and anxiety, increasing patient experience, comfort and satisfaction; 2) Helping patients make their own decisions; 3) Understand the patient's needs holistically, understand the patient's emotions, and respect the patient's choices and wishes; 4) Provide information and education about informed consent, risks and benefits of anesthesia; 5) Involving the patient's family in perioperative. The results of this literatur review prove the important implications of patient centered care in anesthesia. The conclusion from this literature review is that the implications of patient centered care in anesthesia services are very important. This literature review recommends that patient centered care in anesthesia services should be implemented in hospitals.